2019
DOI: 10.2147/idr.s197531
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differential recognition of <em>Candida tropicalis</em>, <em>Candida guilliermondii</em>, <em>Candida krusei</em>, and <em>Candida auris</em> by human innate immune cells</p>

Abstract: Background: The deep-seated infections caused by the Candida genus are associated with a high mortality rate, and Candida albicans is the most frequent species associated with these diseases. The fungal wall is composed of macromolecules not synthesized by the host, and therefore is a source of ligands recognized by innate immune cells. Methods: We performed a comparative study analyzing the cell wall composition and organization of Candida tropicalis, Candida guilliermondii, Candida krusei, and Candida auris,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
99
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 67 publications
(107 reference statements)
12
99
1
1
Order By: Relevance
“…Another study showed that viable C. auris failed to induce a significant inflammatory response in human peripheral blood mononuclear cells (PBMCs), whilst live Candida tropicalis, Candida guilliermondii and Candida krusei induced a much greater release of TNF-α, IL-6 and IL1-β ( Figure 2B). Conversely, heat-killed organisms, including C. auris, stimulated an elevated production of all pro-inflammatory mediators [71]. The authors postulated that heat-inactivation resulted in artificial exposure of chitin and β1,3-glucan on the surface of the cell wall, leading to a dectin-1 receptor stimulation and an elevated immune response as previously described with C. albicans [72].…”
Section: Hide and Seek-immune Evasion Or Lack Of Immune Surveillance?mentioning
confidence: 86%
“…Another study showed that viable C. auris failed to induce a significant inflammatory response in human peripheral blood mononuclear cells (PBMCs), whilst live Candida tropicalis, Candida guilliermondii and Candida krusei induced a much greater release of TNF-α, IL-6 and IL1-β ( Figure 2B). Conversely, heat-killed organisms, including C. auris, stimulated an elevated production of all pro-inflammatory mediators [71]. The authors postulated that heat-inactivation resulted in artificial exposure of chitin and β1,3-glucan on the surface of the cell wall, leading to a dectin-1 receptor stimulation and an elevated immune response as previously described with C. albicans [72].…”
Section: Hide and Seek-immune Evasion Or Lack Of Immune Surveillance?mentioning
confidence: 86%
“…Conversely, such host responses were significantly greater against other Candida species such as Candida tropicalis, Candida guilliermondii and Candida krusei [58]. It is apparent from these studies that the host recognizes yet fails to generate an effective immune response against C. auris .…”
Section: Discussionmentioning
confidence: 99%
“…However, all the C. tropicalis reference strain ATCC 13803 and three clinical isolates (YH50007, YH50013 and YH50114) were sensitive to both P-113 and P-113Tri (Table 2 of [19]). Recently, Navarro-Arias et al compared the content of chitin, mannan, glucan, and phosphomannan on C. tropicalis and C. albicans cell wall and found that there is no significant difference in these two species [56]. However, the porosity of C. tropicalis cell wall is higher than C. albicans (63% vs. 28%) [56], which raises a possibility that P-113 is much easier to gain access into the C. tropicalis cells than P-113Tri due to the small size of P-113 and has a higher activity against C. tropicalis than C. albicans.…”
Section: Discussionmentioning
confidence: 99%